2020
DOI: 10.1038/s41366-020-0572-0
|View full text |Cite
|
Sign up to set email alerts
|

Implication of gut microbiota in the association between infant antibiotic exposure and childhood obesity and adiposity accumulation

Abstract: Background-In animal studies early life antibiotic exposure causes metabolic abnormalities including obesity through microbiota disruption, but evidence from human studies is scarce. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…Across an number of studies, a consistent association has been found between antibiotic-induced changes in the gut microbiota and either childhood adiposity or obesity [ 121 , 122 , 123 , 124 , 125 ]. Zhang and colleagues investigated the influence that prenatal antibiotic exposure had on infant weight for length score (WFL-score), adiposity, and alterations in the gut microbiota [ 121 ].…”
Section: Human Studies Linking Early-life Antibiotic Exposure To Omentioning
confidence: 99%
See 2 more Smart Citations
“…Across an number of studies, a consistent association has been found between antibiotic-induced changes in the gut microbiota and either childhood adiposity or obesity [ 121 , 122 , 123 , 124 , 125 ]. Zhang and colleagues investigated the influence that prenatal antibiotic exposure had on infant weight for length score (WFL-score), adiposity, and alterations in the gut microbiota [ 121 ].…”
Section: Human Studies Linking Early-life Antibiotic Exposure To Omentioning
confidence: 99%
“…Chen et al examined the effect of antibiotic use in the first year of life in a mother-offspring cohort from Singapore and found that antibiotic treatment was associated with altered gut microbiota composition, increased adiposity, and elevated risk of childhood obesity [ 122 ]. Stool samples collected at 24 months of age showed that repeated antibiotic use reduced the microbial co-abundant group (CAG) represented by Eubacterium hallii , which was negatively correlated with childhood adiposity.…”
Section: Human Studies Linking Early-life Antibiotic Exposure To Omentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed informations indicated that gut microbiota is actually related to plasma levels of Se in mice [29]. In this study, Eubacterium_hallii_group had a positive relationship with Se content in the ileum, and it was a member of the butyrate-producers [75][76][77] allowing it to metabolizes glycerol into reuterin [75][76][77]. Stenotrophomonas, an opportunistic pathogen, had a negative relationship with Se content in ileum.…”
Section: Discussionmentioning
confidence: 57%
“…3 These early-life antibiotic exposure could disrupt the gut microbiota, alter the metabolic profile and lead to a higher risk of obesity in later life. 14 Apart from the disease biology, these studies also have important implications on health policies at a population level. As most CRC screening programmes (including that in Singapore) start at the age of 50, these youngonset cancers will be invariably missed.…”
mentioning
confidence: 99%